Bamboo leaf-based carbon dots for efficient tumor imaging and therapy. Issue 67 (14th November 2018) - Fahmi, Mochamad Zakki; Haris, Abdul; Permana, Ahmadi Jaya; Nor Wibowo, Denika Liyan; Purwanto, Bambang; Nikmah, Yatim Lailun; Idris, Adi
Abstract : In this study, carbon dots synthesized from bamboo leaf cellulose were used simultaneously as a staining agent and for doxorubicin delivery to target cancer cells. Abstract : In this study, carbon dots synthesized from bamboo leaf cellulose were used simultaneously as a staining agent and for doxorubicin delivery to target cancer cells. Owing to their nontoxic properties, the production of carbon dots from bamboo leaves is a green approach involving optimized application of bamboo tree waste. For multifunctional applications, the carbon dots were modified with 4-carboxybenzylboronic acid and doxorubicin to improve target specificity and drug delivery to HeLa tumor cells. The resulting modified carbon dots were characterized using different analytical techniques, which showed that they were biocompatible, nontoxic, and highly stable over a wide range of pH values and at high ionic strengths. Furthermore, in vitro confocal microscopy studies demonstrated their blue fluorescence and cellular pathway for entering HeLa cells via folate receptor-mediated endocytosis. Cell viability data and flow cytometry results also confirmed the selective uptake of the carbon dots by HeLa cells, which significantly enhanced cell cytotoxicity.